Using modern reproductive methods to hybridize old and new world Camelids : Camelus dromedarius x Lama guanicoe - J. A. Skidmore; A. M. Billah; W. R. Allen; R. V. Short (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2000)
A group of nine female and one male guanaco were maintained alongside a larger herd of dromedary camels at the Camel Reproduction Centre in Dubai. The ovaries of the female guanacos and camels were scanned regularly, and when they exhibited a dominant follicle of 0.7-0.9 cm diameter in the guanaco, or 1.3-1.8 cm diameter in the dromedaries, they were given a single injection of the GnRH analogue buserelin (Receptal; camels 20 µg i.v., guanacos 10 µg i.m.) to induce ovulation and were inseminated 24 h later. Thirty female dromedaries were inseminated on 50 occasions with 2-4 ml of guanaco semen diluted 1:1 with green buffer (150-400 x 10^6 motile spermatozoa), producing two pregnancies; one resulted in a stillborn on day 365 of gestation, the other was aborted on day 260. Similarly, nine female guanacos were inseminated on 34 occasions with diluted dromedary semen (300-400 x 10^6 motile spermatozoa), which resulted in six conceptions; two were resorbed between days 25-40 after ovulation, two were aborted on days 291 and 302, respectively, one was stillborn on day 365, and one male calf was born live on day 328. To the knowledge of the authors, this is the first ever viable hybrid between Old and New World Camelids. Its existence highlights a remarkable degree of conservation of reproductive processes between them.